2017
DOI: 10.18632/oncotarget.17750
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-1 promotes gastric cancer cell proliferation and invasion via the receptor neogenin through PI3K/AKT signaling pathway

Abstract: Netrin-1 is a laminin-related protein found to promote proliferation and invasion in multiple types of cancers. Recent studies have identified the function role of netrin-1 in several cancers; however, the influence of netrin-1 in human gastric cancer(GC) remains largely unknown. In this study, we found netrin-1 was upregulated in human GC tissues, where its expression correlated inversely with cancer stage and lymph node metastasis. We detected netrin-1 and its receptor knockdown significantly suppressed GC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 33 publications
2
29
0
4
Order By: Relevance
“…In addition, NTN1 has been demonstrated to regulate cancer cell proliferation, migration, invasion and apoptosis (5,8,9,12,13). Our previous study revealed that NTN1 promoted GC cells growth via its receptor neogenin (14); however, the downstream signaling pathway remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, NTN1 has been demonstrated to regulate cancer cell proliferation, migration, invasion and apoptosis (5,8,9,12,13). Our previous study revealed that NTN1 promoted GC cells growth via its receptor neogenin (14); however, the downstream signaling pathway remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that almost 97% of the human genome sequence is transcribed into non-coding RNAs (ncRNAs), and long noncoding RNAs (lncRNAs) are proposed as valuable novel molecules because they are deregulated in many cancers [8,[22][23][24]. For example, Zhang R et al certified that lncRNA TP73-AS1 interacts with miR-142, thus modulating cell growth in brain glioma by activating the HMGB1/RAGE pathway [17].…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT signaling pathway was proven important in the proliferation and metastasis of cancer cells [17]. Our literature research revealed that this is a classic pathway and significant for cancer research because it can promote progression and development of tumors.…”
mentioning
confidence: 97%
“…The constitutive activation of the PI3K/Akt signaling pathway has been noted during the malignant transformation of various cell lines and implicated in carcinogenesis and metastatic potential of human cancer (22). A previous study identified that PI3K/Akt modulated cancer metastasis via the regulation of EMT (23).…”
Section: Discussionmentioning
confidence: 99%